Targeting PPM1D by lentivirus-mediated RNA interference inhibits the tumorigenicity of bladder cancer cells - Wang,W. (2014)
Protein phosphatase magnesium/manganese-dependent 1D (PPM1D) is a p53-induced phosphatase that functions as a negative regulator of stress response pathways and has oncogenic properties. However, the functional role ofPPM1D in bladder cancer (BC) remains largely unknown. In the present study, lentivirus vectors carrying small hairpin RNA (shRNA) targeting PPM1D were used to explore the effects ofPPM1D knockdown on BC cell proliferation and tumorigenesis. shRNA-mediated knockdown of PPM1D significantly inhibited cell growth and colony forming ability in the BC cell lines 5637 and T24. Flow cytometric analysis showed that PPM1D silencing increased the proportion of cells in the G0/G1 phase. Downregulation of PPM1Dalso inhibited 5637 cell tumorigenicity in nude mice. The results of the present study suggest that PPM1D plays a potentially important role in BC tumorigenicity, and lentivirus-mediated delivery of shRNA againstPPM1D might be a promising therapeutic strategy for the treatment of BC.